Features of Fixing the Architectural Heritage in the Belarusian Fine Arts (on the Example of the Exhibition «My Minsk - My Inspiration» - Anton B. Grishchenko (Publishing house "Sreda", 2022)
The exhibition titled «My Minsk - My Inspiration» was organized at the Museum of the History of Minsk and the Belarusian Union of Artists and held in 2021 from September 9 to 26 at the Mikhail Savitsky Art Gallery. This exhibition brought together fine arts and cinema: along with pictorial and graphic works, a number of documentaries in Minsk were presented for viewing, as well as feature films shot especially in Minsk. The purpose of the article is to evaluate paintings and graphic works from the collection of the Belarusian Union of artists presented at the exhibition «My Minsk - my inspiration» in the art gallery of Mikhail Savitsky in Minsk. Created between 1945 and 2018, the mentioned works reflect buildings and streets, valuable in terms of urban development. Paintings have historical and artistic value. The article provides the author's definition of the term «artistic reflection». Based on the method of typing the essence of three artistic reflections of the architectural heritage is revealed: «mirror reflection of artistic heritage», «reflection with the phenomena of artistic reflection» and «fiction in the reflection of the architectural heritage», as well as the identification of works to identify signs of artistic reflection.